1962
DOI: 10.1111/j.1365-2672.1962.tb01132.x
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Group D Streptococci in Cattle and Sheep

Abstract: Numbers and types of Lancefield group D streptococci have been determined in samples from the colons of 17 cattle and 9 sheep. Mean total streptococcal counts of 8 × 104/g in cattle and 2 × 106/g in sheep were obtained. Streptococcus bovis was found in every sample and was the predominant species in 15 of the cattle and 6 of the sheep. Other group D streptococci (Strep. faecalis, Strep. faecium and Strep. durans) were rare in cattle, but in sheep they formed a significant proportion of the population. Of 60 St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

1964
1964
2002
2002

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…About half (53%) of the faecal streptococci found in cattle faeces were identified as S. bovis (Fig. 5), which is similar to the proportions given by Medrek & Barnes (1962), Geldreich & Kenner (1969), Wheater et al (1979), and Pourcher et al (1991). Enterococci, mainly E. durans (34%), dominated in sheep faeces.…”
Section: Animal Faecessupporting
confidence: 81%
“…About half (53%) of the faecal streptococci found in cattle faeces were identified as S. bovis (Fig. 5), which is similar to the proportions given by Medrek & Barnes (1962), Geldreich & Kenner (1969), Wheater et al (1979), and Pourcher et al (1991). Enterococci, mainly E. durans (34%), dominated in sheep faeces.…”
Section: Animal Faecessupporting
confidence: 81%
“…Kenner et al (1960) and Geldreich & Kenner (1969) reported combined percentages of 5. bovis and S. equinus ranging from 18.9% for pigs to 66.2% for cattle with the remaining population in animals appearing to be mainly enterococci. Medrek & Barnes (1962) found that S. bovis was the predominant species in most cattle and sheep. S.faecalis, S.faecium, and S. durans were rare in cattle but formed a significant proportion of the population in sheep.…”
Section: Species Compositionmentioning
confidence: 99%
“…Although enterococci are prevalent in the human intestinal tract, they are less frequently isolated from the animal intestinal tract. E. faecium is the most frequently occurring species in dairy cows (12,19,22,24,26), but E. faecalis, E. hirae, and Enterococcus casseliflavus are also found (10,12). In addition, enterococci are found in water, soil, plants, vegetables, birds, and insects (13,14,16,22).…”
mentioning
confidence: 99%